The Relationship Between Burnout and Juvenile Delinquency in Grade XII Students of the State Islamic High School (MAN) 5 Ciamis in the 2025/2026 Academic Year - Syarifah Hertiningsih; Yandi Cahya Yundani; Ahmad Gojin (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Adolescence is a developmental phase vulnerable to academic pressure and deviant behavior, making burnout and juvenile delinquency a crucial issue in education. This study aims to analyze the relationship between burnout and juvenile delinquency among 12th-grade students at MAN 5 Ciamis in the 2025/2026 academic year. Theoretical studies define burnout as a state of emotional exhaustion, frustration, and decreased motivation due to learning demands, while juvenile delinquency is understood as behavior that violates rules, discipline, and social norms. The study used a quantitative approach with correlational methods and descriptive techniques. Data were collected through a burnout and juvenile delinquency questionnaire, then analyzed statistically. The results showed that student burnout levels were low, while juvenile delinquency was in the moderate category. The correlation test yielded a value of 0.587 with a significance level of 0.000 <0.05, indicating a fairly strong positive relationship. This implies that schools need to strengthen guidance and psychological support services to prevent juvenile delinquency.